PEM fuel cell diagnostic tools - Wang, Haijiang Henry; Yuan, Xiao-Zi; Li, Hui, 1964- (Boca Raton, FL : CRC Press/Taylor & Francis, 2012)
'Volume 2 reviews various tools developed in PEM fuel cell research, for diagnosing the PEM fuel cells and stacks, including in situ and ex situ diagnostic tools, electrochemical techniques and physical/chemical methods, by outlining the principle, experimental implementation, data processing, and the application of each technique. Also, this volume attempts to incorporate the most recent technical advances in PEM fuel cell diagnosis. It discusses capabilities and weaknesses of these techniques'--
'Compared to other electrochemical power devices such as the battery, the PEM fuel cell is much more complicated. Its complexity derives from the following aspects: 1) Most of the components are composite materials. 2) Porous materials must be used for gas and water transport. 3) Nanomaterials have to be used to achieve high electrochemical activity. 4) Complicated processes take place within the fuel cell in addition to the electrochemical reactions, such as the transport of electrons, protons, reactant gases, product water and vapor, and heat. 5) The electrode reaction occurs at a multi-phase boundary and transport may occur across multiple boundaries. 6) Multi-phase flow happens in flow field channels and porous media. 7) The scale at which researchers have to look ranges from nanometers to meters. 8) Three-dimensional architecture is vitally important to performance and durability, due to the large size of PEM fuel cell stacks. 9) Local performance can seriously affect the system's performance and durability. 10) There are complicated operating conditions, such as load, temperature, pressure, gas flow, and humidification'--
Proton exchange membrane fuel cell testing -- Polarization curve -- Electrochemical impedance spectroscopy -- Cyclic voltammetry -- Linear sweep voltammetry -- Current interruption -- Cathode discharge -- Water transfer factor measurement -- Current mapping -- Transparent cell -- Magnetic resonance imaging -- Neutron imaging -- X-ray diffraction -- Scanning electron microscopy -- Transmission electron microscopy infrared imaging -- Fourier transform infrared spectroscopy -- X-ray photoelectron spectroscopy -- Atomic force microscopy -- Binary gas diffusion -- Gas permeability of proton-exchange membranes -- Species detection -- Rotating disk electrode/rotating ring-disk electrode -- Porosimetry and characterization of the capillary properties of gas diffusion media.
Includes bibliographical references and index.
Keywords: Proton exchange membrane fuel cells -- Testing; Proton exchange membrane fuel cells -- Testing -- Equipment and supplies